Analisis Faktor-Faktor Perilaku Konsumen Terhadap Keputusan Pembelian - Anjali Marwiyah Siregar; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
Understanding consumer behavior is very important for entrepreneurs, marketers, and advertising agencies. Understanding how and why consumers make buying decisions will be able to help marketers make the right decisions in their marketing. In this writing, using library research methods, namely research conducted through library materials in the form of scientific writings, journals, articles and research reports that have to do with the topic under study. The data collection technique used is by recording directly from sources of information related to this research. Keywords: Consumer Behavior, Purchase, Factors.